Trade union laws in Malaysia and Japan: A comparative overview - Nik Mahmod, Nik Ahmad kamal bin (Advances in Social Sciences Research Journal, 2020)
Japan history on trade unionism has been imposing. Malaysia’s chapter was fully activated only post-second world war. The ethos of trade unionism ethos differs tremendously between Malaysia and Japan. In the absence of obligations under Convention 87 of the ILO, Malaysia’s treatment on trade unions has been very regimented. The study seeks to evaluate the two different landscapes of law and policy on trade unionism in Malaysia and Japan. The objective is to determine lessons that Malaysia may learn from Japan’s long history of trade unionism law and practice.